2022
DOI: 10.3389/fncel.2022.856734
|View full text |Cite
|
Sign up to set email alerts
|

Sortilin Modulates Schwann Cell Signaling and Remak Bundle Regeneration Following Nerve Injury

Abstract: Peripheral nerve regeneration relies on the ability of Schwann cells to support the regrowth of damaged axons. Schwann cells re-differentiate when reestablishing contact with the sprouting axons, with large fibers becoming remyelinated and small nociceptive fibers ensheathed and collected into Remak bundles. We have previously described how the receptor sortilin facilitates neurotrophin signaling in peripheral neurons via regulated trafficking of Trk receptors. This study aims to characterize the effects of so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 48 publications
(72 reference statements)
0
4
0
Order By: Relevance
“…Seo et al found that, ERK/CREB pathway was inhibited in the model rats with sciatic nerve injury, while exercise training and bone marrow stromal cell implantation could significantly activate ERK/CREB pathway and then promote nerve regeneration ( Seo et al, 2021 ). This process most likely shares a tight relationship with Schwann cell signal transduction ( Ulrichsen et al, 2022 ). The ERK/CREB pathway must also be activated for the nerve regeneration process to take place following a cerebrovascular disease-related nerve injury.…”
Section: Adverse Effects Of Analgesics Related To Nervous Systemmentioning
confidence: 99%
“…Seo et al found that, ERK/CREB pathway was inhibited in the model rats with sciatic nerve injury, while exercise training and bone marrow stromal cell implantation could significantly activate ERK/CREB pathway and then promote nerve regeneration ( Seo et al, 2021 ). This process most likely shares a tight relationship with Schwann cell signal transduction ( Ulrichsen et al, 2022 ). The ERK/CREB pathway must also be activated for the nerve regeneration process to take place following a cerebrovascular disease-related nerve injury.…”
Section: Adverse Effects Of Analgesics Related To Nervous Systemmentioning
confidence: 99%
“…RSCs up-regulate myelin proteins, including neuregulin-1 (NGR-1) type III, adhesion G protein-coupled receptor (GPCR), and tyrosine kinase (Fyn) after reconnecting with axons through activation of multiple signaling pathways, including Par-3/Par-6/aPKC, PI3K/Akt/mTOR, Ga6-Tyro3, NRG-1/ErbB2/3 (Birchmeier and Bennett, 2016;Torii et al, 2019). As a result, RSCs redifferentiate into mSCs, facilitating remyelination of large-caliber axons, while Remak SCs stimulate ensheathing of small-caliber fibers to reform Remak bundles (Ulrichsen et al, 2022).…”
Section: Scs Dedifferentiate and Transdifferentiate Into Rscsmentioning
confidence: 99%
“…NT-3 down-regulation can decrease the myelination of regenerating axons. Furthermore, NT-3/TrkC participates in the regeneration of Remak bundles (Ulrichsen et al, 2022), indicating that reduced NT-3 levels in aging SCs can significantly delay nerve regeneration after PNI. SCs-secreted Btc is significantly up-regulated in injured segments, driving SCs proliferation, thus stimulating their migration, regulating their phenotype, influencing neuron behavior, increasing neurite length, and mediating nerve regeneration.…”
Section: Aging Scs Are Associated With Decreased Secretion Of Neurotr...mentioning
confidence: 99%
“…At the cellular level, Sortilin is involved in the intracellular transport between endoplasmic reticulum (ER), Golgi apparatus, lysosomes, and plasma membrane, regulating multiple biological processes including glucose and lipid metabolism, the trafficking of extracellular vesicles, as well as cell development and cell death [22,28,29]. Sortilin binds a variety of both circulating and transmembrane targets including cytokines, enzymes, peptides, and growth factors [24,25].…”
Section: ]mentioning
confidence: 99%